AB0982 Juvenile Idiopathic Arthritis: Parental Stress Reaction After Diagnosis of a Chronic Desease of their Sons. (9th June 2015) - Dal Forno, I.; Pieropan, S.; Facci, M.; Dosso, G.; Ravagnani, V.; Caramaschi, P.; Biasi, D.; Adami, S.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of diseases characterised by arthritis of unknown origin with onset before age of 16 years. Patients may have high concentrations of positive antinuclear antibodies (ANA) and a high risk of developing chronic iridocyclitis. The chronicity of this illness can affected seriously psychological aspects of these young patients and their parents. Objectives: To evaluate the level of stress among the parents of children affected by JIA and its correlation with the activity and duration of the disease. Methods: 25 parents (mean age of the sons 12 years old) underwent PSI - SF: Parenting Stress Index" (Richard R. Abidin) evaluation; it is a 36 item test drawn in 3 scales to rule out parenting stress, parent and son interaction and eventually type of son according to the point of view of the parent (ie a son with various difficulties); the test may reveal a parental defencive attitude (i.e answers that suggest the creation of a better parental imagine than the reality). The score of the test according to the single scales and the total scale is converted into quintiles and the values above the 85th percentage are significant. The presence of a defencive attitude is confirmed by a score equal or below 10 points. Results: 20% of the parents resulted affected by stress (5 out of 25) A defencive attitude was revealed in 36% of the cases (9 out of 25). 16% of the parents have a difficult interaction with their children (4 out of 25 with the mean age of the children 13, 5 years old and a mean duration of the illness 5, 4 years) 24% of the parents consider their sons having difficulties (6 out of 25 with the mean age of the children 10, 8 years old and a mean duration of the illness 5 years). The overall stress is revealed in 28% of the young population (mean age 11, 4 years old and a mean duration of the illness 5, 7 years). There was no significant difference between the activity of the illness and the presence or not of ocular involvement. Conclusions: Only few parents are stressed by their son diagnosis of JIA. There is however a significant defencive attitude among the parents maybe due to the negation of stress (difficulty of acceptance of a chronic illness?). Parenting stress seems to be higher in the teenage group; it is not worse according to the disease activity or to the presence of ocular involvement. JIA treatment should involve a mulidisciplinary team of caregivers (rheumatologists, pediatricians, phychologysts) in order to cure also the multifaceded psychological aspects of the illness and not least its acceptance by the young patient and by the family. Parental stress if not properly diagnosed and treated may compromise the overall treatment of the JIA as well as the psychological evolution of these young patients in such a critical phase of their life. Disclosure of Interest: None declared